Het Psalter als meerstemmige Thora - Waaijman, Kees (HTS teologiese studies, 2018)
Psalm 1 is generally called the ‘introduction’ to the whole Psalter. At the same time this Psalm is defined as ‘Torah Psalm’ in a narrow sense. By this definition only a few psalms in the Psalter are really Torah Psalms. A ‘Torah Psalm’ as introduction to the Psalter may seem inappropriate. Is Psalm 1 perhaps the wrong ‘introduction’? Alternatively, is our concept of ‘Torah’ inadequate? With this article the researcher attempts to answer these two related questions. Firstly, the concept of ‘Torah’ in the Bible and in the Psalter is reset. Secondly, the key concepts of Psalm 1 are reinterpreted. The outcome is: not only in the Bible and in the Psalter but also in Psalm 1 ‘Torah’ is a multi-dimensional phenomenon. Thus understood, Psalm 1 is a perfect ‘introduction’ to the Psalter.